Digitization of personnel management processes - Pererva, P. G.; Kuchynskyi, Volodymyr (Bydgoszcz University of Science and Technology, Poland, 2021)
The sphere of digitalization of HR at Ukrainian enterprises is currently only at the initial stage of its inception. Less than 10% of them are currently at the stage of modern digitalization, while about 30% still adhere to obsolete paper technologies. Foreign enterprises are far ahead in this area.
Оцифровка процесів управління персоналом
Keywords: monograph; personnel management; processes digitization; transformation; industrial enterprise